Radiation ring with low cracking rate and high consistency and preparation method thereof

CN119340053APending Publication Date: 2025-01-21NINGBO JINJI STRONG MAGNETIC MATERIAL CO LTD

Patent Information

Application Number
CN202411357616.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-21

Smart Images

  • Figure CN119340053A_ABST
    Figure CN119340053A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of permanent magnet materials, and relates to a low-cracking-rate high-consistency radiation ring and a preparation method thereof. The radiation ring is prepared from a second alloy, the chemical formula of the second alloy is Nba1Cob1Al100-a1-b1, 25 < = a1 < = 70, 10 < = b1 < = 60, and a1 + b1 < 100. In the preparation process of the radiation ring, the granularity of fine powder is regulated and controlled, and the granularity uniformity and the powder fluidity of the powder are improved; the pre-sintering time is prolonged, so that Nb and Co elements are more effectively distributed at the grain boundary; meanwhile, a two-stage sintering process is adopted, and the problems that the radiation ring is difficult to burn and poor in density consistency due to addition of a high-melting-point element Nb are solved; the appropriate temperature control cooling rate is adopted, magnetic ring cracking caused by too fast cooling is reduced, and the situation that the Nb-B phase proportion is reduced and the Nb-B phase cannot be evenly distributed on the grain boundary due to too slow cooling is avoided. According to the preparation method, the radiation ring with low cracking rate and high consistency can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of permanent magnet materials and relates to a low-cracking-rate high-consistency radiation ring and a preparation method thereof. Background Art

[0002] At present, most rare earth permanent magnet motors on the market are made of tile-shaped permanent magnets with a single orientation. The air gap magnetic field of the motor using the spliced ​​ring has a tangential flux component, accompanied by a stray magnetic field, which leads to unstable motor output waveform, motor heating and high noise. The flux vector of the radiation ring is completely radial, without a tangential flux component, and there will be no uneven magnetic moment due to geometric tolerances. Compared with conventional spliced ​​magnetic tiles, NdFeB radiation rings are widely used in high-speed motors, tool motors and semiconductor production line systems due to their good magnetic uniformity, good stability, good concentricity, and size matching. With the increasing demand for radial magnetic rings in the high-end application market, domestic companies have carried out research and development of radial magnetic rings and the development of mass production technology.

[0003] Radial ring magnets are characterized by small size and thin ring walls. It is difficult to evenly fill and press the magnetic powder in the mold cavity. In addition, the magnetic field oriented along the radial direction is generally much lower than the parallel oriented magnetic field due to the limitation of the mold's saturated magnetic conductivity, which directly affects the orientation degree of the radial ring and the consistency of the green density. The difference in green density uniformity exacerbates the uneven shrinkage during sintering heating and cooling, resulting in poor magnetic uniformity of the sintered radial ring and easy cracking during sintering and processing. Since the mechanical strength of the NdFeB grain boundary phase is lower than that of the main phase grains, the cracks are usually formed and extended by the grain boundary phase. Therefore, how to improve the toughness of the grain boundary phase and reduce the spread of cracks has become a key research direction for solving the cracking problem of sintered radial rings.

[0004] Ningde Xingyu Technology mentioned in its patent CN109950039A that a rotating pulse magnetic field orientation molding technology is used to make the magnetic powder in the mold cavity fully oriented in the radial direction. Although this technology can solve the technical difficulties of unsaturated and uneven radial orientation in the industrial production of high-performance sintered NdFeB radiation rings, it cannot effectively solve the problems of coil heating and reduced magnetization magnetic field caused by the pulse magnetic field in the batch production process, so it is not suitable for industrial production.

[0005] In patent CN102087917A, Zhongke Sanhuan mentioned that the pre-magnetization technology is adopted in the molding process to improve the orientation degree of the radiation ring, which can improve the magnetic field uniformity and magnetic properties of the radiation ring to a certain extent, but it does not effectively solve the problem of the radiation ring being prone to cracking. Summary of the invention

[0006] In order to solve the above problems existing in the prior art, the object of the present invention is to provide a low cracking rate and high consistency radiation ring and a preparation method thereof, so that the radiation ring has a higher qualified rate and better uniformity.

[0007] One object of the present invention is achieved by the following technical solutions:

[0008] The low cracking rate and high consistency radiation ring is made of alloy 1 and alloy 2. The chemical formula of alloy 1 is (Pr 20 Nd 80 ) a RH b M c B d Fe 100-a-b-c-d , where 28≤a≤33, 0≤b≤4, 0.5≤c≤4, 0.85≤d≤0.95, RH is one or more of Dy, Tb, Ho, Gd, M is one or more of Al, Cu, Ga, Co, Mn, Nb, Zr, Hf, Ti, V; the chemical formula of alloy 2 is Nb a1 Co b1 Al 100-a1-b1 , where 25≤a1≤70, 10≤b1≤60, a1+b1<100.

[0009] Preferably, the chemical formula of alloy 2 is Nb a1 Co b1 Al 100-a1-b1 , where 30≤a1≤60, 20≤b1≤50, a1+b1<100.

[0010] Preferably, the mass of alloy 2 is 1-3 wt % of the total alloy mass.

[0011] The second object of the present invention is achieved by the following technical solutions:

[0012] A method for preparing a low cracking rate and high consistency radiation ring comprises the following steps:

[0013] (1) weighing raw materials according to the chemical molecular formulas of alloy 1 and alloy 2, respectively, and melting and casting the raw materials to obtain casting slab 1 and casting slab 2, respectively;

[0014] (2) mixing the first casting and the second casting, and crushing by hydrogen crushing and jet milling to obtain fine powder;

[0015] (3) adding the powder obtained in step (2) into a radiation ring mold, and molding it in a magnetic field to obtain a green body; inserting a core mold into the green body, vacuum packaging and isostatic pressing to obtain a radiation ring pressed body;

[0016] (4) After the isostatic pressing is completed, the core mold is removed, and the obtained radiation ring compact is subjected to vacuum sintering and tempering to obtain the final radiation magnetic ring.

[0017] Preferably, the smelting temperature of step (1) is 1420-1480°C, the casting temperature is 1400-1450°C, and the thickness of the first and second castings is 0.1-0.6 mm respectively.

[0018] Preferably, in step (2), the mass of the second casting is 1-3wt% of the total mass of the first casting and the second casting; and the surface area average particle size (SMD) of the fine powder obtained by the air flow mill is 3-4 μm.

[0019] Preferably, in step (2), the fine powder obtained by jet milling is classified into magnetic powders D1, D2 and D3 by a powder particle size classifier, and the magnetic powders D1, D2 and D3 are mixed in a ratio of 0wt% < magnetic powder D1 ≤ 20wt%, 50wt% ≤ magnetic powder D2 ≤ 80wt%, and 10wt% ≤ magnetic powder D3 ≤ 30wt% to obtain mixed magnetic powder;

[0020] The particle sizes of the magnetic powders D1, D2 and D3 are respectively D1≤2μm, 2μm<D2<6μm and D3≥6μm.

[0021] Preferably, the magnetic field intensity of step (3) is 1 to 3 T; the pressure of the isostatic pressing treatment is 80 to 300 MPa, and the holding time is 5 to 60 s.

[0022] Preferably, the vacuum sintering process includes: keeping warm at 280-350°C, 400-550°C, and 600-700°C for 1 hour in sequence, dewaxing and dehydrogenation exhaust treatment, then heating to 850-900°C for pre-sintering, the holding time is 6-8 hours, then heating to 1081-1090°C and keeping warm for 0.5-1 hour for the first sintering treatment, naturally cooling to 1040-1080°C and keeping warm for 3-5 hours for the second sintering treatment.

[0023] Preferably, the cooling process after vacuum sintering includes: cooling to 750-850°C at a rate of 1-1.5°C / min, cooling to 350-450°C at a rate of 3-4°C / min, and then cooling to 70°C with argon filling.

[0024] Preferably, the tempering treatment includes two-stage tempering, the first tempering treatment is at a temperature of 880-920° C. and a holding time of 2-3 hours, and the second tempering treatment is at a temperature of 460-550° C. and a holding time of 4-5 hours.

[0025] Preferably, the cooling process in the tempering treatment includes: cooling to 780-810°C at a rate of 1-1.5°C / min after the first tempering, cooling to 380-420°C at a rate of 3-4°C / min, and then cooling to 70°C with argon filling; after the second tempering, cooling to 380-410°C at a rate of 3-4°C / min, and then cooling to 70°C with argon filling.

[0026] In this article, the cooling rate of the argon-filled furnace is approximately 6-8℃ / min, and the specific value is related to the weather and furnace loading.

[0027] Preferably, during the vacuum sintering and tempering treatment, the heating rate is 3-5°C / min.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) The present invention uses a powder particle size classifier to control the particle size of fine powder prepared by a jet mill, which can effectively improve the particle size uniformity and powder fluidity of the powder, reduce the difference in green density consistency caused by powder fluidity during molding orientation and pressing, reduce the internal cracks of the magnetic ring caused by the demolding process, reduce the cracking of the magnetic ring caused by incomplete release of internal stress and uneven shrinkage during sintering, and improve the uniformity of the magnetic properties of the radiation ring;

[0030] (2) The present invention adds the auxiliary alloy NbCoAl and increases the pre-sintering time during the sintering process, so that the Nb and Co elements are more effectively distributed at the grain boundaries, which greatly improves the toughness of the grain boundary phase of the magnetic ring, reduces the shrinkage difference between the inner and outer diameters of the radiation ring, and reduces the intergranular fracture caused by incomplete release of internal stress or shrinkage difference; at the same time, a two-stage sintering process is adopted to reduce the difficult sintering and poor density consistency of the radiation ring caused by the addition of the high melting point element Nb, thereby improving the uniformity of the magnetic properties of the magnetic ring.

[0031] (3) The present invention comprehensively considers the influence of cooling rate on the formation and cracking of Nb-B phase, determines the appropriate temperature-controlled cooling rate, reduces the cracking of the magnetic ring caused by too fast cooling, and avoids the reduction of Nb-B phase ratio and the inability to evenly distribute at the grain boundary caused by too slow cooling. The cracking rate of the radiation ring during sintering is reduced, the toughness of the magnetic ring is improved, and the qualified rate of the post-processing magnetic ring is improved.

[0032] (4) The present invention further prefers that the addition ratio of the auxiliary phase alloy NbCoAl is 1-3%. If the NbCoAl ratio is too low, the Nb element cannot effectively enter the grain boundary; if the addition ratio is too high, due to the high melting point of the auxiliary phase alloy, the Nb element cannot be evenly distributed at the grain boundary during the sintering process, which will reduce the cracking rate of the magnetic ring and the uniformity of the magnetic properties.

[0033] (5) The present invention further preferably has a chemical formula of Nb a1 Co b1 Al 100-a1-b1 , where 30≤a1≤60, 20≤b1≤50, a1+b1<100. Controlling the content of Nb and Co elements in alloy 2 within a certain proportion can effectively improve the cracking rate and magnetic uniformity of the magnetic ring. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 Schematic diagram of the method for detecting the magnetic uniformity of a radiation ring. DETAILED DESCRIPTION

[0035] The technical scheme of the present invention is further described below by specific examples and accompanying drawings. It should be understood that the specific examples described herein are only used to help understand the present invention and are not intended for specific limitations of the present invention. The accompanying drawings used herein are only for better illustrating the disclosure of the present invention and do not have a limiting effect on the scope of protection. If not otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art.

[0036] In the following examples and comparative examples, the lubricant is zinc stearate and the antistatic agent is sodium alkyl sulfonate (prepared by the company).

[0037] Example 1

[0038] In Example 1, the chemical formula of alloy 1 is (Pr 20 Nd 80 ) 31.6 B 0.93 Fe 65.07 Zr 0.1 Nb 0.1 Cu 0.1 Co 1.4 Al 0.4 Ga 0.3 , the chemical formula of alloy 2 is Nb 40 Co 40 Al 20 .

[0039] The method for preparing the radiation ring of this embodiment comprises the following steps:

[0040] (1) weighing raw materials according to the chemical molecular formula of alloy 1 and alloy 2, respectively, and melting (melting temperature 1450° C.) and casting (casting temperature 1420° C.) the raw materials to obtain casting sheet 1 with a thickness of 0.3 mm and casting sheet 2 with a thickness of 0.3 mm, respectively;

[0041] (2) Casting flake 1 and casting flake 2 were mixed in a ratio of 98.5:1.5, and the coarse powder obtained by hydrogen cracking was added with 0.8 g / kg of lubricant and stirred, and then jet milled to obtain fine powder with a SMD of 4.0 μm, and 0.8 g / kg of lubricant and 0.5 g / kg of antistatic agent were added and stirred;

[0042] (3) adding the fine powder obtained in step (2) into a radiation ring mold, and molding it in a magnetic field of 1.5 T to obtain a green body; inserting a core mold into the green body, vacuum packaging and performing isostatic pressing (150 MPa, 15 s) to obtain a radiation ring pressed body;

[0043] (4) After the isostatic pressing is completed, the core mold is removed, and the obtained radiation ring pressed blank is heated at 320°C, 500°C, and 650°C for 1 h at a heating rate of 5°C / min, dewaxing and dehydrogenation exhaust treatment are carried out, the temperature is raised to 880°C for pre-sintering, the temperature is kept for 3 h, and then the temperature is raised to 1075°C for 5 h for sintering. After the sintering is completed, vacuum cooling (cooling rate is about 7°C / min) to 400°C is carried out, and then argon is filled and cooled to 70°C in the furnace;

[0044] (5) Then the temperature is raised to 900°C at 5°C / min and kept at this temperature for 2 h for the first tempering treatment. After the tempering treatment, the mixture is cooled to 400°C in vacuum and then filled with argon and cooled to 70°C in the furnace. The temperature of the second tempering treatment is 515°C and kept at this temperature for 4.5 h. After the tempering treatment, the mixture is cooled to 400°C in vacuum and then filled with argon and cooled to 70°C in the furnace. The final radiation magnetic ring is obtained.

[0045] Example 2

[0046] The difference between Example 2 and Example 1 is that step (2) of Example 2 is: casting sheet 1 and casting sheet 2 are mixed in a ratio of 98.5:1.5, 0.8 g / kg of lubricant is added to the coarse powder obtained by hydrogen cracking treatment, stirred, and then subjected to air flow milling to obtain fine powder with an SMD of 4.0 μm, and the fine powder obtained by air flow milling is classified into magnetic powder D1, D2, and D3 with particle sizes of D1≤2μm, 2μm<D2<6μm, and D3≥6μm by a particle size classifier, and magnetic powders D1, D2, and D3 are mixed in a ratio of D1=10wt%, D2=70wt%, and D3=20wt% to obtain mixed magnetic powder, and 0.8 g / kg of lubricant and 0.5 g / kg of antistatic agent are added to the mixed magnetic powder and stirred evenly.

[0047] The rest is the same as Example 1.

[0048] Example 3

[0049] The difference between Example 3 and Example 2 is that steps (4) and (5) of Example 3 are as follows: after the isostatic pressing is completed, the core mold is removed, and the obtained radiation ring pressed blank is heated at 320°C, 500°C, and 650°C for 1 hour at a heating rate of 5°C / min, dewaxing and dehydrogenation exhaust treatment are carried out, the temperature is raised to 880°C for pre-sintering, the heat preservation time is 3 hours, and then the temperature is raised to 1075°C and the heat preservation time is 5 hours for sintering. After the sintering is completed, the temperature is controlled at a cooling rate of 1.5°C / min to cool to 800°C, and then the temperature is controlled at a cooling rate of 3°C / min. Self-cooling to 400℃, then filling with argon and self-cooling to 70℃ with the furnace; then heating to 900℃ at 5℃ / min and keeping warm for 2h for the first tempering treatment, after which the temperature is controlled to self-cool to 800℃ at a cooling rate of 1.5℃ / min, and self-cool to 400℃ at a cooling rate of 3℃ / min, and then self-cooling to 70℃ with the furnace filled with argon; the temperature of the second tempering treatment is 515℃, and kept warm for 4.5h; after the tempering treatment, the temperature is controlled to self-cool to 400℃ at a cooling rate of 3℃ / min, and then self-cooling to 70℃ with the furnace filled with argon; the final radiation magnetic ring is obtained.

[0050] The rest is the same as Example 2.

[0051] Example 4

[0052] The only difference between Example 4 and Example 3 is the pre-sintering time at 880° C. In step (4) of Example 4, the temperature is raised to 880° C. for pre-sintering, and the holding time is 7 hours.

[0053] The rest is the same as Example 3.

[0054] Example 5

[0055] The only difference between Example 5 and Example 3 is that the high-temperature sintering in step (4) of Example 5 adopts a two-stage sintering process, specifically: after the isostatic pressing is completed, the core mold is removed, and the obtained radiation ring pressed billet is heated at 320°C, 500°C, and 650°C for 1 hour at a heating rate of 5°C / min, dewaxing and dehydrogenation exhaust treatment are carried out, the temperature is raised to 880°C for pre-sintering, and the holding time is 3 hours, and then the temperature is raised to 1088°C and held for 1 hour for sintering, and finally naturally cooled to 1075°C and held for 4 hours for a second sintering. After the sintering is completed, the temperature is controlled to cool to 800°C at a cooling rate of 1.5°C / min, and then the temperature is controlled to cool to 400°C at a cooling rate of 3°C / min, and then argon is filled and the furnace is naturally cooled to 70°C.

[0056] The rest is the same as Example 3.

[0057] Example 6

[0058] The difference between Example 6 and Example 5 is only the time of pre-sintering at 880° C. In step (4) of Example 6, the temperature is raised to 880° C. for pre-sintering, and the holding time is 7 hours.

[0059] The rest is the same as Example 5.

[0060] Comparative Example 1

[0061] The difference between Comparative Example 1 and Example 1 is that there is no alloy 2, and the chemical formula of alloy 1 is (Pr 20 Nd 80 ) 31.1 5B 0.92 Fe 64.03 Zr 0.1 Nb 0.7 Cu 0.1 Co2Al 0.7 Ga 0.3 .

[0062] The preparation method of the radiation ring of Comparative Example 1 comprises the following steps:

[0063] (1) weighing various raw materials according to the chemical molecular formula of alloy 1, and melting (melting temperature 1450° C.) and casting (casting temperature 1420° C.) the various raw materials to obtain a casting sheet 1 with a thickness of 0.3 mm;

[0064] (2) The coarse powder obtained by hydrogenation treatment of the casting sheet was added with 0.8 g / kg of lubricant and stirred, and then pulverized by jet mill to obtain fine powder with SMD of 4.0 μm, and 0.8 g / kg of lubricant and 0.5 g / kg of antistatic agent were added and stirred;

[0065] The subsequent steps are the same as those in Example 1.

[0066] Comparative Example 2

[0067] The difference between Comparative Example 2 and Example 2 is that there is no alloy 2, and the chemical formula of alloy 1 is (Pr 20 Nd 80 ) 31.1 5B 0.92 Fe 64.03 Zr 0.1 Nb 0.7 Cu 0.1 Co2Al 0.7 Ga 0.3 .

[0068] The preparation method of the radiation ring of Comparative Example 2 comprises the following steps:

[0069] (1) weighing various raw materials according to the chemical molecular formula of alloy 1, and melting (melting temperature 1450° C.) and casting (casting temperature 1420° C.) the various raw materials to obtain a casting sheet 1 with a thickness of 0.3 mm;

[0070] (2) The coarse powder obtained by hydrogenation treatment of the casting sheet is added with 0.8 g / kg of lubricant, stirred, and then pulverized by air jet mill to obtain fine powder with SMD of 4.0 μm. The fine powder obtained by air jet mill is classified into magnetic powder D1, D2, and D3 with particle sizes of D1≤2 μm, 2 μm<D2<6 μm, and D3≥6 μm respectively by a particle size classifier. The magnetic powders D1, D2, and D3 are mixed in the ratio of D1=10wt%, D2=70wt%, and D3=20wt% to obtain mixed magnetic powder. 0.8 g / kg of lubricant and 0.5 g / kg of antistatic agent are added to the mixed magnetic powder and stirred evenly.

[0071] The subsequent steps are the same as those in Example 2.

[0072] Comparative Example 3

[0073] The difference between Comparative Example 3 and Example 3 is that there is no alloy 2, and the chemical formula of alloy 1 is (Pr 20 Nd 80 ) 31.1 5B 0.92 Fe 64.03 Zr 0.1 Nb 0.7 Cu 0.1 Co2Al 0.7 Ga 0.3 .

[0074] The preparation method of the radiation ring of Comparative Example 3 comprises the following steps:

[0075] (1) weighing various raw materials according to the chemical molecular formula of alloy 1, and melting (melting temperature 1450° C.) and casting (casting temperature 1420° C.) the various raw materials to obtain a casting sheet 1 with a thickness of 0.3 mm;

[0076] (2) The coarse powder obtained by hydrogenation treatment of the casting sheet is added with 0.8 g / kg of lubricant, stirred, and then pulverized by air jet mill to obtain fine powder with SMD of 4.0 μm. The fine powder obtained by air jet mill is classified into magnetic powder D1, D2, and D3 with particle sizes of D1≤2 μm, 2 μm<D2<6 μm, and D3≥6 μm respectively by a particle size classifier. The magnetic powders D1, D2, and D3 are mixed in the ratio of D1=10wt%, D2=70wt%, and D3=20wt% to obtain mixed magnetic powder. 0.8 g / kg of lubricant and 0.5 g / kg of antistatic agent are added to the mixed magnetic powder and stirred evenly.

[0077] The subsequent steps are the same as those in Example 3.

[0078] Comparative Example 4

[0079] The difference between Comparative Example 4 and Example 4 is that there is no alloy 2, and the chemical formula of alloy 1 is (Pr 20 Nd 80 ) 31.1 5B 0.92 Fe 64.03 Zr 0.1 Nb 0.7 Cu 0.1 Co2Al 0.7 Ga 0.3 .

[0080] The preparation method of the radiation ring of Comparative Example 4 comprises the following steps:

[0081] (1) weighing various raw materials according to the chemical molecular formula of alloy 1, and melting (melting temperature 1450° C.) and casting (casting temperature 1420° C.) the various raw materials to obtain a casting sheet 1 with a thickness of 0.3 mm;

[0082] (2) The coarse powder obtained by hydrogenation treatment of the casting sheet is added with 0.8 g / kg of lubricant, stirred, and then pulverized by air jet mill to obtain fine powder with SMD of 4.0 μm. The fine powder obtained by air jet mill is classified into magnetic powder D1, D2, and D3 with particle sizes of D1≤2 μm, 2 μm<D2<6 μm, and D3≥6 μm respectively by a particle size classifier. The magnetic powders D1, D2, and D3 are mixed in the ratio of D1=10wt%, D2=70wt%, and D3=20wt% to obtain mixed magnetic powder. 0.8 g / kg of lubricant and 0.5 g / kg of antistatic agent are added to the mixed magnetic powder and stirred evenly.

[0083] The subsequent steps are the same as those in Example 4.

[0084] Comparative Example 5

[0085] The difference between Comparative Example 5 and Example 5 is that there is no alloy 2, and the chemical formula of alloy 1 is (Pr 20 Nd 80 ) 31.1 5B 0.92 Fe 64.03 Zr 0.1 Nb 0.7 Cu 0.1 Co2Al 0.7 Ga 0.3 .

[0086] The preparation method of the radiation ring of Comparative Example 5 comprises the following steps:

[0087] (1) weighing various raw materials according to the chemical molecular formula of alloy 1, and melting (melting temperature 1450° C.) and casting (casting temperature 1420° C.) the various raw materials to obtain a casting sheet 1 with a thickness of 0.3 mm;

[0088] (2) The coarse powder obtained by hydrogenation treatment of the casting sheet is added with 0.8 g / kg of lubricant, stirred, and then pulverized by air jet mill to obtain fine powder with SMD of 4.0 μm. The fine powder obtained by air jet mill is classified into magnetic powder D1, D2, and D3 with particle sizes of D1≤2 μm, 2 μm<D2<6 μm, and D3≥6 μm respectively by a particle size classifier. The magnetic powders D1, D2, and D3 are mixed in the ratio of D1=10wt%, D2=70wt%, and D3=20wt% to obtain mixed magnetic powder. 0.8 g / kg of lubricant and 0.5 g / kg of antistatic agent are added to the mixed magnetic powder and stirred evenly.

[0089] The subsequent steps are the same as those in Example 5.

[0090] The difference between Examples 7-13 and Comparative Examples 6-8 and Example 6 is the difference in the composition and / or proportion of Alloy 1 and Alloy 2, as shown in Table 1 below:

[0091] Table 1

[0092]

[0093]

[0094] The radial orientation magnetic ring measurement samples with specifications of D35*D27.5*21.5 were prepared by inner and outer grinding and end grinding, and magnetic uniformity and consistency were tested. The specific testing method is: using a magnetic field strength tester, at every 2mm in the height direction, continuously testing the radial ring surface magnetism along the circumferential direction and forming a magnetic field strength waveform as a testing uniformity method, see for details Figure 1 Magnetic uniformity = (maximum surface magnetism - minimum surface magnetism) / average surface magnetism * 100%.

[0095] Multiple batches of tests were conducted according to Comparative Examples 1-8 and Examples 1-13, and the results are shown in Table 2.

[0096] Table 2

[0097]

[0098]

[0099] By comparing Comparative Examples 1-5, it can be seen that the conventional process of using a single alloy of a radiation-oriented magnetic ring, through the control of powder particle size and the use of a temperature-controlled self-cooling process, can improve the pass rate and magnetic uniformity of the magnetic rings to a certain extent, but extending the pre-sintering time has little effect on the pass rate and uniformity of the magnetic rings, and the use of a two-stage sintering process will reduce the pass rate of the magnetic rings. By comparing Comparative Examples 1-5 and Examples 1-5, it can be seen that the addition of the auxiliary phase alloy NbCoAl can effectively improve the pass rate of the magnetic rings and improve the magnetic uniformity. And unlike the conventional process, after adding NbCoAl, the pre-sintering and two-stage sintering processes can be used to further improve the pass rate and consistency of the magnetic rings.

[0100] Comparing Examples 6-8, it is found that when the addition ratio of the auxiliary phase alloy NbCoAl is too low, the Nb element cannot effectively enter the grain boundary, the toughness of the grain boundary phase is limited, and the improvement on the cracking rate of the magnetic ring is limited; when the addition ratio is too high, due to the high melting point of the auxiliary phase alloy, the Nb element cannot be evenly distributed at the grain boundary during the sintering process, and the aggregation is more serious, which will have a negative impact on the subsequent uniform shrinkage of the magnetic ring and the toughness of the grain boundary phase. Therefore, the cracking rate of the magnetic ring and the uniformity of the magnetic properties will decrease.

[0101] Compared with Examples 6, 9-12, the NbCoAl content design of Alloy 2 has a greater impact on the cracking rate and magnetic uniformity of the magnetic ring. According to current research, the Nb element is evenly distributed at the grain boundary, which can effectively improve the toughness of the grain boundary phase, and the Co element is distributed at the grain boundary phase to reduce the difference in shrinkage between the inner and outer diameters of the magnetic ring. Therefore, the content of the two elements in the composition design of Alloy 2 needs to reach a certain ratio, but too high a content will lead to too high a melting point of the alloy, and the elements cannot be effectively distributed at the grain boundary during the sintering process, which has limited improvement on the toughness and magnetic uniformity of the magnetic ring. When Alloy 2 is Nb, Co, and Al alone (Comparative Examples 6-8), the toughness and magnetic uniformity of the magnetic ring are greatly reduced relative to Example 6.

[0102] The various aspects, embodiments, and features of the present invention should be considered to be illustrative in all aspects and not limiting of the present invention, the scope of which is defined solely by the claims. Other embodiments, modifications, and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0103] In the preparation method of the present invention, the order of each step is not limited to the order listed. For those skilled in the art, without creative work, the order of each step is also within the protection scope of the present invention. In addition, two or more steps or actions can be performed simultaneously.

[0104] Finally, it should be noted that the specific embodiments described herein are merely examples of the present invention, and are not intended to limit the implementation methods of the present invention. A person skilled in the art of the present invention may make various modifications or supplements to the specific embodiments described, or replace them in a similar manner. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.

Claims

1. Low cracking rate and high consistency radiation ring, characterized by: The raw materials for its preparation include alloy 1 and alloy 2. The chemical formula of alloy 1 is (Pr 20 Nd 80 ) a RH b M c B d Fe 100-a-b-c-d , where 28≤a≤33, 0≤b≤4, 0.5≤c≤4, 0.85≤d≤0.95, RH is one or more of Dy, Tb, Ho, Gd, M is one or more of Al, Cu, Ga, Co, Mn, Nb, Zr, Hf, Ti, V; the chemical formula of alloy 2 is Nb a1 Co b1 Al 100-a1-b1 , where 25≤a1≤70, 10≤b1≤60, a1+b1<100.

2. The radiation ring according to claim 1, characterized in that: The chemical formula of alloy 2 is Nb a1 Co b1 Al 100-a1-b1 , where 30≤a1≤60, 20≤b1≤50, a1+b1<100.

3. The radiation ring according to claim 1, characterized in that: The mass of alloy 2 is 1-3wt% of the total alloy mass.

4. The method for preparing a low cracking rate and high consistency radiation ring according to claim 1, characterized in that: The following steps are involved: (1) weighing raw materials according to the chemical molecular formulas of alloy 1 and alloy 2, respectively, and melting and casting the raw materials to obtain casting slab 1 and casting slab 2; (2) mixing the first casting and the second casting, and crushing by hydrogen crushing and jet milling to obtain fine powder; (3) adding the powder obtained in step (2) into a radiation ring mold, and molding it in a magnetic field to obtain a green body; inserting a core mold into the green body, vacuum packaging and isostatic pressing to obtain a radiation ring pressed body; (4) After isostatic pressing, the core mold is removed, and the obtained radiation ring compact is subjected to vacuum sintering and tempering to obtain the final radiation magnetic ring.

5. The preparation method according to claim 4, characterized in that: In step (2), the mass of the second casting is 1 to 3 wt% of the total mass of the first casting and the second casting; The surface area average particle size of the fine powder obtained by jet milling is 3 to 4 μm.

6. The preparation method according to claim 4, characterized in that: In step (2), the fine powder obtained by jet milling is classified into magnetic powders D1, D2, and D3 by a powder particle size classifier, and the magnetic powders D1, D2, and D3 are mixed in a ratio of 0wt% < magnetic powder D1 ≤ 20wt%, 50wt% ≤ magnetic powder D2 ≤ 80wt%, and 10wt% ≤ magnetic powder D3 ≤ 30wt% to obtain mixed magnetic powder; The particle sizes of the magnetic powders D1, D2 and D3 are respectively D1≤2μm, 2μm<D2<6μm and D3≥6μm.

7. The preparation method according to claim 4, characterized in that: The vacuum sintering process includes: keeping warm at 280-350℃, 400-550℃, and 600-700℃ for 1h in sequence, dewaxing and dehydrogenation exhaust treatment, then heating to 850-900℃ for pre-sintering, the holding time is 6-8h, then heating to 1081-1090℃ for 0.5-1h for the first sintering treatment, naturally cooling to 1040-1080℃ for 3-5h for the second sintering treatment.

8. The preparation method according to claim 7, characterized in that: The cooling process after vacuum sintering includes: cooling to 750-850°C at a rate of 1-1.5°C / min, cooling to 350-450°C at a rate of 3-4°C / min, and then cooling to 70°C with argon filling.

9. The preparation method according to claim 4, characterized in that: The tempering treatment includes two-stage tempering. The temperature of the first tempering treatment is 880-920°C and the insulation time is 2-3 hours. The temperature of the second tempering treatment is 460-550°C and the insulation time is 4-5 hours.

10. The preparation method according to claim 9, characterized in that: The cooling process in the tempering treatment includes: cooling to 780-810°C at a rate of 1-1.5°C / min after the first tempering, cooling to 380-420°C at a rate of 3-4°C / min, and then cooling to 70°C with argon filling; after the second tempering, cooling to 380-410°C at a rate of 3-4°C / min, and then cooling to 70°C with argon filling.

Citation Information

Patent Citations

  • Preparation method and pressing device for radiation-oriented magnet ring or multipolar magnet ring

    CN102087917A

  • Forming device of sintered neodymium iron boron radiation ring and radiation ring preparation method

    CN109950039A

Cited By

  • Selective laser pre-strengthening thin and high ring anti-cracking sintering method

    CN120940650A